Adherence to the Clinical Good Practical Guide of Bronchial Asthma in the Allergy Consultation - Marisela Pérez Pacaréu; Rafael Zamora Puerta; Magalys Olivares Elegia; Rosa Naranjo Revollido (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: Bronchial asthma constitutes a high prevalence disease which gets the 10 % of our milieu. That's why it is very important to assess its clinical management. The clinical good practice guide constitutes a group of orientations which outline the medical assistance based on what is considered as the best options for treatment and diagnosis. Objective: to determine the adherence of the medical personnel specialized on the clinical good practical guide in the diagnosis and treatment of intercrisis bronchial asthma in ambulatory patients. Methods: A descriptive study was performed at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ in Cienfuegos city where 300 clinical records of allergic patients attending consultation during November 2001 to December 2005 were assessed. The questionnaire was applied to verify the level of general and partial fulfilment of the guide. Results: The main errors detected in the partial adherence were: Not to evaluate the asthmatic patient according to the criteria of high risk (90 % of partial adherence) and lack of assessment of the patients of asthmatic high risk in the multidisciplinary consultation in which only the 70 % is adherenced to the guide. Conclusions: The general adherence to the guide was of 100% with highly significant results and a satisfactory evaluation.